Digital preservation in the context of institutional repositories in public universities' libraries in Ghana. - Mensah, Monica (The Balme Library, University of Ghana, 2015)
Long-term preservation of digital collections is an integral task for institutional repositories. It ensures that the digital intellectual output of the library is preserved for future access. Digital preservation has been recognized as a complex process, and there are still many unsolved issues which makes it a challenging task for institutional repositories. As such, this paper is aimed at identifying and discussing the issues and challenges of digital preservation facing institutional repositories in public university libraries in Ghana. The study was qualitative. Data used for analysis were drawn from respondents from public universities who had developed institutional repositories to capture, maintain and disseminate their information in the digital form. The key finding of the study was that, although the universities had established institutional repositories to capture and maintain digital collections, existing digital preservation methods and systems were inadequate and could lead to consequences such as denial of access to their digital collections or total loss of information. Recommendations based on findings included the development of comprehensive digital preservation policies to provide mandate and direction to preservation of the libraries digital collections.
Keywords: Digital Preservation; Institutional Repositories; Public Universities; Libraries; Ghana